Promote Good Governance in Public Financial: The Practice of Local Budget (APBD) Transparency Through Open Data Jakarta in Jakarta Provincial Government - Dodi Faedlulloh; Fetty Wiyani (Jurnal Good Governance, 2019)
This paper aimed to explain public financial governance based on good governance implementation in Jakarta Provincial Government. This paper specifically discussed towards transparancy implementation of local budget (APBD) through open data portal that publishes budget data to public. In general, financial transparency through open data has met Transparency 2.0 standards, namely the existence of encompassing, one-stop, one-click budget accountability and accessibility. But there are indeed some shortcomings that are still a concern in order to continue to maintain commitment to the principle of transparency, namely by updating data through consistent data visualization.Transparency of public finance needs to continue to be developed and improved through various innovations to maintain public trust in the government.Keywords: Public Finance, Open Data, Transparency